(untitled) (Al-Academy, 2019)
The interpretation is one of the means used to by the designer to construct his perceptions of the world in which he lives, either to better understand or rediscover or reproduce the new thing and the creative thing which is characterized by novelty and originality. The design innovations in the political posters, achieved by the designer, result from his perceptions for the response towards a certain subject through what he has of practical experience to interpret his ideas and his desire to achieve harmony with the reality and compatibility with his aims in visible visual effects that will be established in the recipient’s memory and stimulate his senses in the realization of the content of the media message. The political poster has a great role in coding design ideas, and designers often use symbols and signals that have political connotations. Usually, many political posters in countries that lack freedom of opinion are banned because they tackle the political situation through presentation. The theoretical framework included the first section (the intellectual concepts of interpretation in the graphic design) and the second section (the effectiveness of interpretation in the design of political posters). The researcher, after the analysis, reached a set of results, the most important of which is that: the effectiveness of interpretation requires reading the forms, and requires considering the process of understanding itself, and the creative thinking depends on the active imagination, which is characterized by the production of new unprecedented images and combinations. Finally the research ended with the conclusions in which goals set were achieved.